Trade With India And China - Roett, Riordan, 1938-; Paz, Guadalupe, 1970-; Kahn, Theodore (Washington, D.C. : Brookings Institution Press, 1829)
"How an evolving relationship with China and India is changing Latin America's political and economic dynamics. In the years since China has adopted a "going global" strategy to promote its overseas investment, expand export markets, and gain much-needed access to natural resources abroad, Sino-Latin American relations have both deepened and broadened at an unexpectedly rapid pace. The main driver behind this sea change in bilateral relations has been economic complementarity, with resource-rich countries in Latin America exporting primary goods to the Asian giants' growing market and China exporting manufactured goods back into the region. In recent years, Sino-Latin American relations have matured considerably, becoming far more nuanced and multifaceted than ever before. India is a relatively new player in the region, but has slowly strengthened its ties. As one of Asia's largest markets, it offers interesting parallels to the Chinese case. Will Indo-Latin American ties follow a similar path? The main areas of growth include trade and investment, mining, energy, information technology, motor vehicle production, and pharmaceuticals. To what extent these changing dynamics will redefine Latin America's relations with India is a question of increasing relevance for policymakers. This volume offers a review of key cross-regional trends and critical policy issues involving the changing relationship between these two Asian giants and Latin America. Selected country case studies-Argentina, Brazil, Chile, and Mexico-provide a more in-depth analysisof the implications of China's and India's evolving interaction with the region"--
Introduction : assessing Latin America's relations with the Asian giant / Guadalupe Paz -- Latin America looks to Asia : integration, cooperation, and geopolitical goals / Riordan Roett -- Recasting South-South links : Indo-Latin American relations / Jorge Heine and Hari Shesasayee -- Sino-Latin American relations from a Chinese perspective / Sun Hongbo -- China goes geopolitical in its strategic partnership with Latin America / Xiang Lanxin -- A Latin American perspective on China's growing presence in the region / Jorge Guajardo -- Latin America's China decade : managing benefits and risks / Kevin P. Gallagher and Rebecca Ray -- Recalibrating Indo-Latin American policy / Deepak Bhojwani -- India's interaction with Argentina, Brazil, Chile, and Mexico / Rengaraj Viswanathan -- Seeking a better deal for Latin America : new opportunities or more of the same? / Anthony Boadle -- Latin America's changing energy landscape : assessing the implications of new Asian players / Francisco Gonzalez -- Latin America at the frontline of food security? / Mariano Turzi -- Latin American trade with India and China : the region needs a "business plan" / Robert Devlin and Theodore Kahn -- Migration in a mobile age : perspectives from China, India, and the Americas / Jacqueline Mazza -- The security dimension of Chinese and Indian engagement in the Americas / R. Evan Ellis -- Chile : a bridge to Asia? / Alicia Frohmann and Manfred Wilhelmy -- Mexico's relationship with China and India : recent developments / Enrique Dussel Peters -- Argentina and Brazil : towards an Atlantic strategy? / Henrique Altemani de Oliveira -- Future scenarios for Latin America's relations with China and India / Mauricio Mesquita Moreira and Theodore Kahn.
Includes bibliographical references and index.
Keywords: POLITICAL SCIENCE / International Relations / Trade & Tariffs; POLITICAL SCIENCE / Globalization; POLITICAL SCIENCE / International Relations / General; Latin America -- Foreign economic relations -- China; China -- Foreign economic relations -- Latin America; Latin America -- Foreign economic relations -- India; India -- Foreign economic relations -- Latin America